Metagenomics Approaches to Investigate the Neonatal Gut Microbiome - Boudar, Zakia; Sehli, Sofia; El Janahi, Sara; Al Idrissi, Najib; Hamdi, Salsabil; Dini, Nouzha; Brim, Hassan; Amzazi, Saaïd; Nejjari, Chakib; Lloyd-Puryear, Michele; Ghazal, Hassan (Frontiers in Pediatrics, 2022)
Early infancy is critical for the development of an infant's gut flora. Many factors can influence microbiota development during the pre- and postnatal periods, including maternal factors, antibiotic exposure, mode of delivery, dietary patterns, and feeding type. Therefore, investigating the connection between these variables and host and microbiome interactions in neonatal development would be of great interest. As the "unculturable" era of microbiome research gives way to an intrinsically multidisciplinary field, microbiome research has reaped the advantages of technological advancements in next-generation sequencing, particularly 16S rRNA gene amplicon and shotgun sequencing, which have considerably expanded our knowledge about gut microbiota development during early life. Using omics approaches to explore the neonatal microbiome may help to better understand the link between the microbiome and newborn diseases. Herein, we summarized the metagenomics methods and tools used to advance knowledge on the neonatal microbiome origin and evolution and how the microbiome shapes early and late individuals’ lives for health and disease. The way to overcome limitations in neonatal microbiome studies will be discussed.